Sourdough [compact disc, unabridged] : a novel - Sloan, Robin, 1979- (Macmillan Audio, 2017)
A software engineer is left a sourdough starter from sibling bakers after they're forced to close their shop, a gift that leads to a new vocation, a legal dispute, and a venture into a secret market that fuses food with technology.